(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2018)
A field trial was conducted to evaluate the comparative effects of jatropha seedcake, chicken and kraal manures on selected soil properties, growth and yield of tomato in Zambia during the cropping season of 2012-13. A Randomized Complete Block Design (RCBD) with four replicates and six treatments, namely- jatropha seedcake (5.0 t ha-1), chicken manure (5.0 t ha-1), kraal manure (5.0 t ha-1), jatropha seedcake (2.5 t ha-1) + chicken manure (2.5 t ha-1), jatropha seedcake (2.5 t ha-1) + kraal manure (2.5 t ha-1) and control (0.0 t ha-1) was used. Soil total N, P, K, Ca, Mg, SOM, soil pH, bulk density, plant height, number of branches, number of fruits plant-1, and mean fruit weight effects were subsequently monitored. Organic manures significantly increased total N, available P, exchangeable K, Ca, Mg, SOM, soil pH, plant height, number of branches, number of fruits, mean fruit weight and yield of tomato compared to the control. Organic manures also significantly reduced soil bulk density compared to the control. Among the organic amendments treated alone, jatropha seedcake gave the highest yield of 28.62 t ha-1 compared to chicken manure (28.20 t ha-1) and kraal manure (27.50 t ha-1). Maximum yield benefits came from a mixture of jatropha seedcake + chicken manure (29.60 t ha-1)and jatropha seedcake + kraal manure (29.00 t ha- 1) which could have been due to balanced proportions of major nutrients required for tomato growth. Jatropha seedcake mostly performed favourably the same or better than chicken and kraal manures in many aspects. Int. J. Agril. Res. Innov. & Tech. 8 (1): 1-6, June, 2018